The Effect of Electronic Word Of Mouth, Product Quality, Promotion and Price on Interest in Buying MSME Products in Malang After The Covid 19 Pandemic - Moh Cholid Mawardi; Sudarmiatin Sudarmiatin; Agus Hermawan (Universitas Trunodjoyo Madura, 2023)
The research aims to find out and analyze how the electronic word of mouth, the quality of products, prices and promotion of the interest in the prebujaya outfit buy products. The sample used in this study is 105 respondents who once made a purchase at a poor prebujaya outfit. The method of data analysis used in the study is a quantitative data analysis that USES linear regression analysis. The data testing used was the simultaneous hypothesis (f) and the testing of a partial hypothesis (t) from simultaneous tests showing that the electronic word of mouth, product quality, promotion, and price affected the interest of buying. Based on partial testing of electronic word of mouth variables can make a significant difference to purchasing interest, product quality variables have a significant impact on purchasing interests, promotional variables have a significant impact on purchasing interests, and price variables affect the interest of the purchase.